Desain Kelembagaan Pembiayaan Perang Pada Masa Nabi Muhammad Saw: Analisis Historis Terhadap Ghanimah Dan Fai’ Dalam Pembentukan Ketahanan Fiskal Negara Madinah - Putri Rauzatul Jannah; Muhammad Maulana; Nur Fadhilah Handayani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
. This study aims to analyze the institutional design of war financing during the time of the Prophet Muhammad (peace be upon him) through the instruments of ghanimah and fai’ and their contribution to the formation of the fiscal resilience of the State of Medina. This study is motivated by the still limited research discussing ghanimah and fai’ from the perspective of fiscal institutions and state asset management. The study uses a qualitative method with a library research approach sourced from the Qur'an, hadith, Islamic historical literature, and various relevant scientific journals. The analysis is conducted through a historical and conceptual approach to reconstruct the management mechanism of ghanimah and fai’ in the Medina fiscal system. The results show that there was a transformation in the management of war assets from an individualistic ‘urf pattern to a structured institutional system oriented towards the public interest. Ghanimah and fai’ functioned not only as sources of state revenue but also as instruments for the distribution and redistribution of wealth that supported social justice, political stability, and public welfare. In addition, the implementation of the asset allocation and reallocation system, especially through the productive management of fai’ lands, successfully established a sustainable war financing cycle and strengthened the state's fiscal capacity. This instrument also serves as the basis for developing military infrastructure, providing state liquidity, and maintaining defense readiness without burdening the public with high taxes. These findings confirm that the success of the fiscal resilience of the State of Medina was built through the integration of sharia principles, effective public asset governance, and sustainable defense financing strategies. This research contributes to the enrichment of Islamic economics literature, particularly regarding the concept of state fiscal policy and public asset management from an Islamic historical perspective.